2021
DOI: 10.3390/healthcare9050594
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward Aging Mediates the Relationship between Personality and Mental Health in Older Adults

Abstract: This study aimed to examine attitude toward aging as a potential mediator of the relationship between personality factors and mental health in terms of depression and life satisfaction among older adults. A cross-sectional study was conducted with 438 Ethiopian elderly individuals aged 60 to 69. The results of the regression-based path analysis showed that after adjusting for demographic data, the relationship between agreeableness and depression in older adults was partially mediated by attitude toward aging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Moreover, a previous study has revealed the negative impact of internalized stigma on the quality of life of people with serious mental (30) and chronic (31) illnesses. In addition, a recent study found that attitude toward own aging was a potential mediator in the relationship between personality factors and mental health and life satisfaction among older adults (32). Another study reported that attitude to aging moderated the relationship between subjective age and psychological wellbeing (33).…”
Section: The Moderating Effect Of Attitudes Toward Aging In the Relat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a previous study has revealed the negative impact of internalized stigma on the quality of life of people with serious mental (30) and chronic (31) illnesses. In addition, a recent study found that attitude toward own aging was a potential mediator in the relationship between personality factors and mental health and life satisfaction among older adults (32). Another study reported that attitude to aging moderated the relationship between subjective age and psychological wellbeing (33).…”
Section: The Moderating Effect Of Attitudes Toward Aging In the Relat...mentioning
confidence: 99%
“…This study found that negative attitudes toward own aging moderated the association between self-perceived stigma and quality of life. Results of the simple slope analysis showed that the stronger effect of self-perceived stigma on the quality of life among older adults exists along with more negative attitudes toward own aging, which refers to negative attitudes and beliefs toward older adults or toward the aging process itself (32). Older adults with a positive attitude toward their own aging are more likely to combat external stigma better, regulate their negative emotions openly, maintain health-promoting behaviors and lifestyles, and more easily make efforts to integrate into modern society (61).…”
Section: Attitudes Toward Own Aging Moderated the Relationship Betwee...mentioning
confidence: 99%
“…Previous research has found that senior citizens with a positive aging attitudes report higher levels of mental health and better quality of life ( Low et al, 2013 ; Bedaso and Han, 2021 ). In contrast, a negative concept of aging can result in physically frail and lower subjective well-being ( Brown et al, 2016 ; Gale and Cooper, 2018 ).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Geriatric healthcare needs are diverse and multi-level, and they vary significantly among different age groups. The influence of healthcare for the elderly is influenced by a combination of many factors such as age, place of residence, education level and psychological status ( 11 13 ). Specifically, it is reflected in many aspects such as economic factors, policy factors, and social support.…”
Section: Introductionmentioning
confidence: 99%